The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1001/jamainternmed.2022.5600
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Racial, and Ethnic Representation in COVID-19 Clinical Trials

Abstract: ImportanceSince the onset of the COVID-19 pandemic, there have been calls for COVID-19 clinical trials to be fully representative of all demographic groups. However, limited evidence is available about the sex, racial, and ethnic representation among COVID-19 prevention and treatment trials.ObjectiveTo investigate whether female participants and racial and ethnic minority individuals are adequately represented in COVID-19 prevention and treatment trials in the US.Data SourcesIdentified studies were registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 61 publications
1
32
1
1
Order By: Relevance
“…This might be explained by the public policies and guidelines from the National Health Institute to enhance the participation of racial and ethnic groups and other minorities in clinical trials (36). However, reporting does not necessarily imply better representativeness, as suggested by a recent study that found underrepresentation of Black and Asian groups in trials about COVID-19 prevention (37). The representativeness of a trial not only depends on who is included, but also on who completed the follow-up (38).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the public policies and guidelines from the National Health Institute to enhance the participation of racial and ethnic groups and other minorities in clinical trials (36). However, reporting does not necessarily imply better representativeness, as suggested by a recent study that found underrepresentation of Black and Asian groups in trials about COVID-19 prevention (37). The representativeness of a trial not only depends on who is included, but also on who completed the follow-up (38).…”
Section: Discussionmentioning
confidence: 99%
“…The underrepresentation has even persisted in large-scale US-based COVID-19 trials, including the phase 3 Blocking Viral Attachment and Cell Entry with SARS-CoV-2 Neutralizing Antibodies trial (NCT04427501) for the monoclonal antibody combination bamlanivimab plus etesevimab, in which only 12.6% of patients self-identified as non-White [ 15 ], and the Pfizer-BioNTech and Moderna vaccine trials in which patients self-identifying as non-White represented 18.1% and 20.6% of the trial cohorts, respectively [ 12 ]. Furthermore, in a systematic review and meta-analysis of 122 US-based COVID-19 trials, Xiao et al described aggregate differences in trial representation relative to COVID-19 incidence between racial/ethnic groups in both vaccine and treatment studies [ 13 ]. Amid a global pandemic that disproportionately affects communities of color [ 18 ], opportunities for early access to potentially effective treatments through trials, coupled with the need for findings that are generalizable to those bearing the greatest burden of COVID-19, necessitate diverse trial enrollment and the addressing of factors that discourage participation by underrepresented groups.…”
Section: Discussionmentioning
confidence: 99%
“…The underrepresentation of minoritized groups in health research is well established (18)(19)(20). The reasons for this lack of representation are not singular; they can be attributed to distrust of health research, lack of opportunity, and structural barriers.…”
Section: Why Should Race-based Data Be Collected In Health Research?mentioning
confidence: 99%